Adapting the primary Mathematics curriculum to the multigrade classroom in rural Sri Lanka. - Vithanapathirana, M.V. (My University, 2006)
This chapter is based on an action research project with teachers in multigrade schools in a rural Education Zone in Sri Lanka. The objectives of this chapter is to present the small-scale intervention made to improve multigrade practice, which in turn is hoped to raise the awareness of policy makers on multigrade teaching. The study originated as a part of the multi-site international research project on multigrade teaching (www.ioe.ac.uk/multigrade). The chapter incorporates the setting for multigrade teaching in the country, an analysis of the primary curriculum with special reference to Mathematics, the innovation planned through adaptation of the Mathematics curriculum for multigrade lesson planning, the intervention ,made in collaboration with the teachers in adopting the innovation the innovative strategy and the impact of the intervention. Lastly, pointers to further research and development measures are given.